Spatial variability of physical attributes of a Oxisol related to garlic productivity - Teixeira de Oliveira, Job; Alves de Oliveira, Rubens; Milena Rojas Plazas, Gloria; Garcia Roque, Cassiano (Revista Brasileira de Engenharia de Biossistemas, 2023)
Garlic is a product with high demand in Brazil and worldwide, being highly valued in the cuisine of several countries and is a culture with high added economic value. In 2018, this work was carried out in the irrigation and drainage area of the Federal University of Viçosa, in Viçosa, Minas Gerais State, Brazil, in a Oxisol. The objective was to characterize the structure and magnitude of the spatial distribution of physical attributes of a Oxisol, perform the mapping, and evaluate the spatial correlation between garlic bulb yield, lateral shoot growing and soil characteristics. The attributes studied were garlic bulb yield, lateral shoot growing, soil moisture on a dry basis, soil moisture on a humid basis, volumetric soil moisture, particle density, free soil porosity, sampled in a 90-georeferenced grid. Data analysis using statistical techniques and geostatistics made it possible to verify that the garlic yield and other soil physical attributes studied showed spatial dependence. There was an emphasis on the spatial correlation between garlic bulb yield and free-soil porosity. The lateral shoot growing of garlic has a direct and positive relationship with free soil porosity, soil moisture on a dry basis and soil moisture on a humid basis.